Understanding urban wage inequality in China 1988 - 2008: Evidence from quantile analysis - Simon Appleton; Lina Song; Qingjie Xia (Institute for the Study of Labor (IZA), 2012)
This paper examines change in wage gaps in urban China by estimating quantile regressions on CHIPS data. It applies the Machado and Mata (2005) decomposition, finding sharp increases in inequality from 1988 to 1995 and from 2002 to 2008 largely due to changes in the wage structure. The analysis reports how the returns to education and experience vary across wage quantiles, along with wage differentials by sex and party membership. The role of industrial structure, ownership reform and occupational change are also estimated. In the recent period, 2002 to 2008, falls in the returns to education and experience have been equalising. However, changes in every other category of observed wage differential - by sex, occupation, ownership, industrial sector and province - have served to widened inequality. The gender gap continued to rise, as did the gap between white collar and blue collar workers, and between manufacturing and most other industrial sectors.
Keywords: J31; J42; O15; P23; 330; China; labour; wages; quantile regression; inequality; Lohnstruktur; Lohndifferenzierung; Städtischer Arbeitsmarkt; Schätzung; China